Synthesis of acrolein by oxidative coupling of alcohols over spinel catalysts: microcalorimetric and spectroscopic approaches. Issue 6 (25th February 2020) - Folliard, Vincent; Postole, Georgeta; Marra, Livia; Dubois, Jean-Luc; Auroux, Aline
Abstract : Oxidative coupling of methanol and ethanol is becoming a promising alternative to produce sustainable acrolein. Abstract : Oxidative coupling of methanol and ethanol is becoming a promising alternative to produce sustainable acrolein. In this work, the reaction has been performed in two successive reactors (for oxidation and aldolization respectively) in order to study the role of the acid/base properties of spinel catalysts with various Al/Mg ratios. The acid/base properties of catalysts were investigated by NH3 and SO2 adsorption microcalorimetry. To deeply investigate the adsorption mechanism of the reactants on the catalysts, other adsorption microcalorimetry studies coupled to FTIR were performed using methanol, formaldehyde, acetaldehyde and propionaldehyde. Catalytic results were correlated to FTIR spectra and revealed the disproportionation of formaldehyde. Co-adsorption of aldehydes was also investigated by FTIR showing a preferential adsorption of formaldehyde compared to acetaldehyde. The different species resulting from aldehyde adsorption are discussed.